Radon (222Rn) Radioactivity Level at the BATAN Workplace using RAD7 - Arsita sita; Dahlang Tahir; June Mellawati; R Pradana (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2020)
Measurement of Radon (222Rn) radioactivity level at BATAN office Jakarta has been done. Radon is a radioactive emitting alpha particle, very dangerous to the health because if it is inhaled, will be accumulated in the lungs and cause lung cancer. The purpose of the research was to determine the activity concentration of 222Rn in the workplace and to estimate the dose received by workers. The sampling method is purposive sampling, in several office rooms of the BATAN office (staff room, laboratory, and warehouse), measurement 222Rn using RAD7 continuously for 24 hours. Based on the activity concentration of 222Rn in the rooms, an estimate of the effective dose received by the workers while working indoors can be calculated. The results showed that exposure of 222Rn gas radiation in the workplace was relatively varied, radiation exposure in warehouses was 18.90-32.90 (25.90) Bq.m-3 higher than in laboratory 8.20-34.00 (22.43) Bq.m-3 and staff room 5.40-29.60 (16.68) Bq.m-3. The estimated effective dose received by workers in the warehouse is 0.1865 mSv.year-1, laboratory 0.1615 mSv.year-1, and in the staff rooms 0.1267 mSv.year-1, and this value still meets the quality standards of radiation exposure required by the Ministry of Health No. 7 of 2019 and is categorized as safe.